Improving accessibility and livability in Amauta park (Cusco) - Aramburú Naveda, Lena (2025)
This study assesses accessibility in Amauta Park, Cusco, identifying architectural barriers that hinder inclusion for people with reduced mobility. Using a qualitative approach, accessibility regulations were analyzed, and solutions based on universal design were proposed. A verification matrix with 20 criteria from Technical Standard A.120 was applied, resulting in a global compliance of 15%, calculated through itemized evaluation and double inter-rater validation. The methodological limitations are also acknowledged, highlighting the need for clearer operational metrics. Results underscore the need for inclusive interventions. Recommendations include accessible routes, multisensory signage, and adapted furniture to ensure habitability and promote equality in public spaces.